Early marginal bone stability of dental implants placed in a transalveolarly augmented maxillary sinus: a controlled retrospective study of surface modification with calcium ions - Eduardo Anitua; Laura Piñas; Mohammad Hamdan Alkhraisat (SpringerOpen, 2017)
Abstract Background Recently, components of the extracellular cellular matrix have been assessed to enhance the biological response to dental implants. This study aims to assess the effect of surface modification with calcium ions on the early marginal bone loss of dental implants placed in a transalveolarly augmented maxillary sinus. Methods A retrospective study of transalveolar sinus floor augmentation was conducted in a single private dental clinic. The predictor variable was the surface of the dental implant. The primary outcome was the marginal bone loss. The secondary outcomes were the intraoperative complications and the dental implant failure. Descriptive analysis was performed for patients' demographic data and implant details. Results Fifty-one patients with a mean age of 58 ± 11 years had a mean follow-up time of 13 months. Thirty-four dental implants had a Ca2+-modified hydrophilic surface, and 31 had no Ca2 (control). The experimental group showed a statistically significant lower marginal bone loss (0.36 ± 0.42 vs 0.61 ± 0.39 mm). However, there were no statistically significant differences in the implant survival. No implant failed in the experimental group while two implants failed in the control group. Conclusions The modification of an acid-etched surface with calcium ions seems to reduce the marginal bone remodeling around the dental implants, placed after transalveolar sinus floor elevation.